HAK ATAS TANAH YANG JANGKA WAKTUNYA SUDAH HABIS DIWARISKAN KEPADA AHLI WARIS (STUDI KASUS HAK GUNA BANGUNAN NOMOR 111/KWITANG) - Carissa Janice; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Building rights title can be terminated due to its period of time. The land will be returned to its owner when the period of time is over. However, there’s some building rights title whose period of time is over that is still be included in some certificate of inheritance or wills although according to Law Number 5 of 1960 also referred to as UUPA or the Basic Agrarian Law Act the land has to be returned to the state or to its owner. Can building rights title which has expired be inherited by the heirs? And how is the dividing method? The research data shows that there are some different opinions from the results of the interview about the expiration time of building rights title. Building rights title that has expired cannot be extended but rights renewal can be done. Therefore, the building tights title is requested for rights renewal only then be divided according to its rightful heirs.